MATHEMATICAL APPROACH FOR PILOT-SCALE EXPERIMENT SETUP ON BIOGAS PRODUCTION - CIOABLĂ, Adrian Eugen; IVANOVICI, Mădălina; DUMITREL, Gabriela-Alina; ORDODI, Laurențiu-Valentin; CĂLINOIU, Delia-Gabriela; TRIF-TORDAI, Gavrilă; PODE, Vasile (Studia Universitatis Babeș-Bolyai Chemia, 2020)
In this work, pilot scale experiments were carried to evaluate the biogas production through anaerobic co-digestion for two different mixtures of feedstock based on agricultural biomass and agricultural waste. The first mixture consisted of degraded row barley and wastewater from treatment plant and the second mixture contained wheat, corn grains and shell sunflower seeds with wastewater from treatment plant. The temperature, pH, pressure and the amount of the produced biogas were daily monitored for 26 days and the results of the two experimental charges were assessed and compared using statistical analysis: the box plot method and summary statistics. The latter feedstock mixture showed a better production of biogas for which the mean value of produced biogas amount is 18.43 m³, whereas the mean value of the biogas generated for the former feedstock mixture was 14.95 m³.